Pengaruh Kelekatan Orang Tua dan Kecerdasan Emosi terhadap Agresivitas Remaja - Pramudita, Aisyah; Nurfadillah, Nurfadillah; Jannah, Miftachul; Riany, Yulina Eva (Indonesian Journal of Educational Counseling, 2024)
In the evolution of individual personality, the adolescent phase holds unique and critical significance as during this period, adolescents have various responsibilities, including exploring and establishing their identity. Parents play a vital role during this phase as adolescents tend to have a high level of curiosity, which can lead to negative actions or aggressive behavior. This research aims to determine the correlation between parental attachment and emotional intelligence on adolescent aggression in Bogor. Aggressive behavior is a significant contributor factor to the high morbidity and mortality rates among adolescents worldwide. This research utilizes a quantitative correlational research method. The sampling technique used in this study is the convenience sampling method. The research was conducted from October to November 2023, with respondents from SMA Plus Bina Bangsa Sejahtera students. The research findings indicate that among the respondents, 25 percent fell under the insecure attachment category, 64 percent fell within the moderate aggression category, followed by 7 percent who fell under the high aggression category, while the remaining respondents were under the low aggression category. In conclusion, this study highlights the importance of parental attachment and emotional intelligence in adolescent aggression. The findings show that secure attachment and high emotional intelligence play an important role in reducing aggressive behavior among adolescents.